The effect of endurance training on mitochondrial function in Siberian huskies and Alaskan huskies - Sælen-Helgesson, Silje (UiT Norges arktiske universitet, 2023)
Teams of Alaskan huskies and Siberian Huskies are used to pull sleds and compete in long-distance races such as Finnmarksløpet (1200 km) and the Iditarod (1600 km). That is an elite athlete performance, and their ability to conduct such extreme endurance challenges under arctic conditions is poorly understood. A previous study has shown that Alaskan huskies possibly have the highest values of mitochondrial oxidative phosphorylation (255±38 pmol/s*mg) and electron transfer system (254±37 pmol/s*mg) ever recorded in a mammalian skeletal muscle. This current study aimed to determine respiratory capacity in skeletal muscles from Siberian huskies and Alaskan huskies, off-season (August) and at the end of the racing season (March/April) to highlight physiological adaptations in the respiratory capacity of skeletal muscles arising as a result of selective breeding amongst huskies, as well as potential difference in the acclimatization responses to endurance training. Micro biopsy samples from M. biceps femoris were taken from non-raced and raced Siberian huskies and Alaskan huskies (2022–2023), and tissue homogenates were prepared for high resolution respirometry analyzes as well as citrate synthase activity assays to determine mitochondrial density. Respiratory capacity in skeletal muscle mitochondria from Siberian huskies and Alaskan huskies was higher during racing season as compared to off-season. Group mean values of electron transfer system (E) and oxidative phosphorylation (P) for were (P: 175.2±89.5, E: 164.2±92.1 pmol/s*mg) for raced Alaskan huskies and (P: 190.4±52.9, E: 180.0±56.7 pmol/s*mg) for raced Siberian huskies. The increase in aerobic capacity possibly results from a measured increase in muscle mitochondrial density, indicating a clear acclimatization response to endurance training. Alaskan huskies were shown to have higher respiratory capacity in their skeletal muscles as compared to that of Siberian huskies, based on carbohydrates associated substrates, possibly due to difference in their genetics. ...